Männer der Revolution von 1848. Redaktion: K. Obermann, G. Becker, S. Schmidt [u.a. Mit Beitrn von J. Strey, W. Schmidt, M. Häckel u.a.]. Mit 14 Abbn (Akademie-Verlag, 1970)
Hrsg. vom Arbeitskreis Vorgeschichte und Geschichte der Revolution von 1848/49.